Root growth and nutrient accumulation in cover crops as affected by soil compaction - Rosolem, Ciro Antonio [UNESP]; Foloni, J. S S [UNESP]; Tiritan, C. S. [UNESP] (Elsevier, 2002)
Crop rotation using cover crops with vigorous root systems may be a tool to manage soils with some degree of compaction. Root and shoot growth as well as nutrient accumulation by summer species suitable for crop rotation in tropical areas were studied at different subsoil compaction levels. Crotalaria juncea (Indian hemp), Crotalaria spectabilis (showy crotalaria), Helianthus annuus (sunflower), Pennisetum americanum (pearl millet) and Sorghum bicolor (guinea sorghum) were grown for 40 days in pots 33.5 cm high with 10 cm internal diameter. Soil in the pots had uniform bulkdensity of 1.25 Mg m-3 for the top and bottom 15 cm sections. Bulk densities of 1.31, 1.43, 1.58 and 1.70 Mg m-3 Were established in the 3.5 cm middle section. H. annuus and P. americanum had the highest early macronutrient accumulation. The grasses S. bicolor and P. americanum yielded twice as much shoot dry matter as the other species. Root growth generally decreased with increasing soil bulk density with C. spectabilis less affected than other species. Although the grasses were more sensitive to high soil penetration resistance, they showed higher root length densities at all compaction levels. P. americanum had the highest potential to be used as cover crop due to its high root density at high soil penetration resistances, vegetative vigour and ability to accumulate macronutrients. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Biopores; Cover crops; Crop rotation; Roots; Soil bulk density; bulk density; compaction; cover crop; crop rotation; nutrient; root system; soil property; Apocynum cannabinum; Cannabis; Cannabis sativa; Crotalaria; Crotalaria juncea; Crotalaria spectabilis; Helianthus; Helianthus annuus; Hibiscus cannabinus; Pennisetum; Pennisetum glaucum; Poaceae; Sorghum bicolor